2017
DOI: 10.1016/j.jinorgbio.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Heterolytic OO bond cleavage: Functional role of Glu113 during bis-Fe(IV) formation in MauG

Abstract: The diheme enzyme MauG utilizes H2O2 to perform oxidative posttranslational modification on a protein substrate. A bis-Fe(IV) species of MauG was previously identified as a key intermediate in this reaction. Heterolytic cleavage of the O-O bond of H2O2 drives the formation of the bis-Fe(IV) intermediate. In this work, we tested a hypothesis that a glutamate residue, Glu113 in the distal pocket of the pentacoordinate heme of MauG, facilitates heterolytic O-O bond cleavage, thereby leading to bis-Fe(IV) formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…MauG was prepared as described previously [1, 2, 4, 7, 9, 27]. Briefly, P. denitrificans cells carrying a plasmid for expression of MauG were grown in mineral salts medium at 30°C in 4 stages: 10 ml, 100 ml, 1 L, and 10 L. Tetracycline at 2 μg/ml was used for antibiotic selection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MauG was prepared as described previously [1, 2, 4, 7, 9, 27]. Briefly, P. denitrificans cells carrying a plasmid for expression of MauG were grown in mineral salts medium at 30°C in 4 stages: 10 ml, 100 ml, 1 L, and 10 L. Tetracycline at 2 μg/ml was used for antibiotic selection.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysate was clarified by centrifugation, and the supernatant was collected. The His 6 -tagged MauG was purified by nickel affinity chromatography, desalted to remove excess imidazole, and concentrated by ultrafiltration as described previously [7, 9, 27]. All reactions were carried out in 50 mM potassium phosphate buffered to pH 9.0 for optimized intermediate production.…”
Section: Methodsmentioning
confidence: 99%
“…At the active site, two conserved residues, Glu118 and Gln108, are proposed to play an important role in the formation and stabilization of the oxoferryl (Fe 4+ -oxo) intermediate species and Glu118, in particular, in the cleavage of the hydrogen peroxide O-O bond. An identical role was proposed for a conserved glutamate residue in the heme cavity of MauG proteins, which has a similar heme cavity to BCCPs [ 35 , 36 , 37 ]. The importance of these two residues in catalysis was proven by site-directed mutagenesis studies, which showed that these single residue variants were inactive [ 20 ].…”
Section: Discussionmentioning
confidence: 85%